Ukraine : First Review Under the Standii-By Arrangement-Staff Report; Staff Statement; Press Release on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Ukraine's 29-month Stand-By Arrangement (SBA) was approved. Ukraine's satisfactory performance under the economic program supported by the Stand-By Arrangement, along with strong policy commitments for the coming year, are supporting a steady recovery in confidence and broadening of economic activity. Further efforts, including gas price increases and structural reforms, are needed to create a more viable and transparent energy sector. Important progress has been made in rehabilitating and restoring confidence in the financial system, including private bank recapitalization and steps toward strengthening the supervisory framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet